Tumor Arrests DN2 to DN3 Pro T Cell Transition and Promotes Its Conversion to Thymic Dendritic Cells by Reciprocally Regulating Notch1 and Ikaros Signaling - Guha, Ipsita; Bhuniya, Avishek; Shukla, Divanshu; Patidar, Ashok; Nandi, Partha; Saha, Akata; Dasgupta, Shayani; Ganguly, Nilanjan; Ghosh, Sweta; Nair, Arathi; Majumdar, Subrata; Saha, Bhaskar; et al. (Frontiers in Immunology, 2020)
Tumor progression in host leads to severe impairment of intrathymic T cell differentiation/maturation, leading to the paralysis of cellular anti-tumor immunity. Such suppression manifests the erosion of CD4+CD8+ double positive (DP) immature thymocytes and a gradual increase in CD4-CD8- double negative (DN) early T cell progenitors. Impact of such changes on T cell progenitor pool in the context of cancer remains poorly investigated. Here, we show that tumor progression blocks Lin-Thy1.2+CD25+CD44+c-KitlowDN2b to Lin-Thy1.2+CD25+CD44-c-Kit-DN3 transition in T cell maturation, instead lead to DN2-T cell differentiation into dendritic cells (DC). We observed that thymic IL-10 expression is upregulated, particularly at cortico-medullary junctions (CMJ) under conditions of progressive disease, resulting in the termination of IL-10Rhigh DN2-T cell maturation due to dysregulated expression of Notch1 and its target CCR7 (thus restricting these cells to the CMJ). Intrathymic differentiation of T cell precursors in IL-10-/- mice and in vitro fetal thymic organ cultures revealed that IL-10 promotes the interaction between thymic stromal cells and Notch1low DN2-T cells, thus facilitating these DN2-T cells to differentiate towards CD45+CD11c+MHC-II+ thymic DCs as a consequence of activating the Ikaros/IRF8 signaling axis. We conclude that a novel function of thymically-expressed IL-10 in the tumor-bearing host diverts T cell differentiation towards a DC pathway, thus limiting the protective adaptive immune repertoire.